2019
DOI: 10.1002/hpm.2926
|View full text |Cite
|
Sign up to set email alerts
|

Organisational antecedents of workplace victimisation: The role of organisational climate, culture, leadership, support, and justice in predicting junior doctors' exposure to bullying at work

Abstract: Workplace bullying is a pervasive phenomenon among junior doctors that may negatively impact their training and abilities to deliver quality healthcare, yet evidence on the factors of bullying among them remains lacking. This study examined the role of organisational climate, culture, leadership, support, and justice in junior doctors' exposure to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 120 publications
0
19
1
Order By: Relevance
“… 45–47 Health workers in China and Japan reported prevalence rates using the NAQ-r of 5.6%–18.5%. 48 , 49 A recent investigation from Malaysia found that 13% of junior doctors reported bullying in the workplace using the NAQ-r. 28 …”
Section: Discussionmentioning
confidence: 99%
“… 45–47 Health workers in China and Japan reported prevalence rates using the NAQ-r of 5.6%–18.5%. 48 , 49 A recent investigation from Malaysia found that 13% of junior doctors reported bullying in the workplace using the NAQ-r. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Work environment is another antecedent of the concept of workplace cyberbullying 10 . Samsudin et al 44 identified factors including organizational climate, working culture, leadership, support, and justice play a role in workplace victimization. An organization climate that is high‐pressured, extremely competitive, competitive, and strained with inadequate support contributes to an increase in workplace cyberbullying 10,44 .…”
Section: Antecedents and Consequencesmentioning
confidence: 99%
“…Samsudin et al 44 identified factors including organizational climate, working culture, leadership, support, and justice play a role in workplace victimization. An organization climate that is high‐pressured, extremely competitive, competitive, and strained with inadequate support contributes to an increase in workplace cyberbullying 10,44 . Organizational culture defined as “shared basic assumptions, values, and beliefs” that are shared with newcomers may have unwritten sets of rules and norms that influence the behavior of the workgroup, which may include organizational tolerance for bullying 44 .…”
Section: Antecedents and Consequencesmentioning
confidence: 99%
See 2 more Smart Citations